Assessment of myocardial function by two-dimensional speckle tracking echocardiography in patients with Kawasaki disease: a mid-term follow-up study - Wang, Haiyong; Tong, Minghui; Mu, Jingjing; Wu, Tingting; Ruan, Litao (Coronary artery disease, 2021)
Myocardial impairment proved by histological studies persists in late convalescent phase Kawasaki disease patients. Whether Kawasaki disease-induced myocardial lesions can be detected in an earlier time is not well explored. In this study, we aimed to evaluate left ventricular (LV) myocardial function by two dimensional speckle tracking echocardiography (2DSTE) in late convalescent phase Kawasaki disease patients. A total of 68 Kawasaki disease patients during mid-term phase including 47 with no coronary artery aneurysm (NCAA) and 21 with coronary artery aneurysm (CAA), and 60 controls with age matched were consecutively enrolled. No significant differences on conventional echocardiographic LV systolic function indices were found among group comparison. Compared with controls, Kawasaki disease patients had lower global longitudinal stain (GLS) and global circumferential stain (GCS). In subgroup analysis, both those with CAA and without CAA had lower GLS, lower GCS, higher amino-terminal propeptide of type III procollagen (PIIINP) and higher carboxyterminal propeptide of procollagen type I (PIPC) than in controls. GLS had significantly negative correlations with PIIINP (r = -0.69, P = 0.002) and PIPC (r = -0.82, P = 0.000). Subclinical myocardial dysfunction in mid-term follow-up Kawasaki disease patients existed regardless of coronary artery status despite normal measurements of LV systolic function by routine echocardiography, and myocardial fibrosis may play a contributed role in this subclinical myocardial function impairment. 2DSTE is a valuable imaging modality for detecting regional and global myocardial dysfunction in Kawasaki disease patients in an early time.